Misinterpretation of Genomic Data Matters for Endangered Species Listing: The Sub-specific Status of the Peñasco Least Chipmunk (Neotamias minimus atristriatus) - Hope, Andrew G.; Frey, Jennifer K. (Frontiers in Conservation Science, 2022)
Abstract.—Puckett et al. (2021. Ecology and Evolution, 11, 12114-12128) evaluated the subspecies status of the Peñasco least chipmunk (Neotamias minimus atristriatus) using genomic approaches and concluded that their results did not support the distinction of this taxon as a subspecies and recommended it be synonymized with N. m. operarius. We refute the interpretations, conclusions, and taxonomic recommendations of Puckett et al. (2021), and explain in clearer terms how to interpret genomic analyses for applied management. We identify four broad conceptual issues that led to errant recommendations: 1) interpretation of subspecies and diagnosability, 2) inappropriate use of reciprocal monophyly as a criterion for subspecies, 3) importance of geographic isolation, and 4) error in hypothesis testing and misinterpretation of results. We conclude that the data of Puckett et al. (2021) add to information from prior studies providing strong support for recognition of N. m. atristriatus as a subspecies. This finding has important and immediate implications for the proposed listing of N. m. atristriatus as an endangered species under the U.S. Endangered Species Act.